Additive manufacturing of tantalum scaffolds: Processing, microstructure and process-induced defects. (April 2023) - Aliyu, Abdul Azeez Abdu; Poungsiri, Kitti; Shinjo, Junji; Panwisawas, Chinnapat; Reed, Roger C.; Puncreobutr, Chedtha; Tumkanon, Krittima; Kuimalee, Surasak; Lohwongwatana, Boonrat
Abstract: Extreme melting point, high density, and ease of oxidation of tantalum (Ta) make its processing rather difficult using conventional methods. Additive manufacturing (AM) serves as an alternative Ta processing technique with unique design flexibility, customization, and minimizing material wastage. However, most additively manufactured parts contain undesired microstructural features or deviations (process-induced defects). This study aimed to assess the processability of the solid and structurally porous scaffolds of Ta through laser powder-bed fusion (LPBF) AM. It will further characterize and evaluate microstructure of LPBF processed Ta, with emphasis on assessing the mechanism of the process-induced defects. The x-ray diffraction (XRD) and microstructural investigation confirmed the presence of BCC Ta phase containing columnar, equiaxed and fine grains with roughness between 3.88 nm to 10.40 nm. The presence of oxygen resulted in the formation of some oxide phases such as Ta2 O5 and Ta2 O3 . Numerous process-induced defects, including solidification-induced micropores, pores-induced and solidification-induced microcracks were identified. The dislodge unmelted or partially fused Ta powder resulted in other form of defects including micro-concaves and microgrooves. The mechanism of pore formation during the LPBF of Ta was assessed through computational simulation and its findings rationalised the experimental results. Graphical abstract: Unlabelled Image Highlights: Highly dense and porous scaffolds of tantalum was successfully processed through laser powder-bed fusion process. The final microstructure of the laser powder-bed fusion processed tantalum contained equiaxed, columnar and fine grains. The formation mechanism of process-induced defects during laser powder-bed fusion of tantalum was assessed. Tantalum specimens processed through borderline parameter conditions have more process-induced defects.